The “lost diaries” of Manuela Sáenz in the Development of a Cultural Icon - Hennes, Heather (2009)
The author highlights the influence of Manuela Sáenz’ “lost diaries” on three texts: Diario de Paita (edited by Carlos Álvarez Saá), the biography promoted by the Manuela Sáenz Museum (Quito) and the Venezuelan film by Diego Rísquez. She explains that advocates of civic and feminist causes have made use of Sáenz as a symbol conveying an image of a daring transgressor of gender roles, sexually corrupt, and disruptive of social order. However, the museum and the Rísquez film would portray her as honorable, insisting on her persevering love and loyalty to Bolívar. Hennes believes that Rísquez’ approach to gender and sexuality issues duly respects the complexity and integrity of Sáenz in film and History. Her gender performance, Hennes claims, enables her to frequent male and female scenarios and become a figure of political and social influence within Bolívar’s circle. The image of Bolívar as a tragic figure would be a feature shared by Diario de Paita and the film but absent in the Museum’s literature. In spite of their differences, the three texts contribute to an ongoing construction of a political, social and cultural icon.